Formulasi, Stabilitas, dan Uji Aktivitas Krim Tabir Surya dari Ekstrak Batang Kaktus (Opuntia Cochenillifera (L.) Mill) Menggunakan Spektrofotometer Ultraviolet-Visible. - Samsuar Samsuar; Nopiayansyah Nopiayansyah; Indra Hidayatullah (Jurnal Penelitian Pendidikan IPA, 2026)
Sunlight has several health benefits, but it also has certain negative impacts. Sunscreen is a cosmetic product that protects the skin from ultraviolet rays, which can cause a number of skin health problems. Phenolic compounds, particularly flavonoids, have the potential to be used in sunscreen cosmetics. The goal of this research is to develop a sunscreen cream using the active ingredient Centong cactus stem extract (Opuntia cochenillifera (L.) Mill) and evaluate its stability and Sun Protection Factor (SPF) using a spectrophotometer. The results showed that the formulation of Centong cactus stem extract sunscreen cream met the criteria set regarding its physical and chemical properties based on the Indonesian National Standard (SNI) 2016-4399-1996. These properties include organoleptic characteristics, homogeneity, spreadability, adhesion, pH, viscosity, and stability. The sunscreen activity test resulted in an SPF rating of 7.04 ± 0.32 for the first f ormulation (FI) for extra protection, 12.02 ± 0.34 for the second formulation (FII) for maximum protection, and 18.03 ± 0.31 for the third formulation (FIII) for ultra protection. The results of this initial study indicate that Centong cactus stem extract sunscreen cream has good stability and ultra-sun protection factor FIII (15%) activity, which is very good for further research.